Simplifying
3x + 25 = 2x + 20
Reorder the terms:
25 + 3x = 2x + 20
Reorder the terms:
25 + 3x = 20 + 2x
Solving
25 + 3x = 20 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
25 + 3x + -2x = 20 + 2x + -2x
Combine like terms: 3x + -2x = 1x
25 + 1x = 20 + 2x + -2x
Combine like terms: 2x + -2x = 0
25 + 1x = 20 + 0
25 + 1x = 20
Add '-25' to each side of the equation.
25 + -25 + 1x = 20 + -25
Combine like terms: 25 + -25 = 0
0 + 1x = 20 + -25
1x = 20 + -25
Combine like terms: 20 + -25 = -5
1x = -5
Divide each side by '1'.
x = -5
Simplifying
x = -5